PERTANGGUNGJAWABAN BANK ATAS PELANGGARAN KERAHASIAAN DATA PRIBADI MILIK NASABAH YANG DILAKUKAN PEGAWAI BANK BERDASARKAN UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 10 TAHUN 1998 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 7 TAHUN 1992 TENTANG PERBANKAN - Merta Merta; Amad Sudiro (Fakultas Hukum Universitas Tarumanagara, 2021)
In conducting business activities, especially in banking, there are regulations whereby banks must provide correct, clear and honest information regarding the conditions and guarantees of goods and / or services as well as provide explanations for the use, repair and maintenance and also must not leak customer personal data. However, there is still leakage of customer personal data by bank employees. The main issues are: 1) How is the bank accountable for the confidentiality of customer personal data carried out by bank employees based on Law of the Republic of Indonesia Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 concerning Banking? 2) How to take legal remedies by customers for the management of confidentiality of customer personal data by bank employees based on Law of the Republic of Indonesia Number 10 of 1998 concerning Amendments to Act Number 7 of 1992 concerning Banking? The researcher examines the problem using normative legal research methods and uses an invitation-only approach, a case approach and a conceptual approach. Data from the incident research show that Maybank Indonesia must be responsible for the losses incurred by Winda D Lunardi as a customer. Maybank Indonesia should have provided clear and complete information to customers.